Analysis of Indoor Thermal Comfort of Room Space in the International Standard Hotel Building - Sahid, Nasrullah; Rahim, Ramli; Hamzah, Baharuddin; Mulyadi, Rosady (Advances in Social Sciences Research Journal, 2019)
The objective of this study was to analyze the indoor thermal comfort of room space international standard hotel buildings. The sample of the study was guests staying at five international standard hotels. The total sample were 1,092 people from five international standard hotels then sampling through Slovin formula of 10% to determine the number of respondents as many as 92 respondents. Primary data was collected through survey and questionnaires. Data was analyzed with software regarding air temperature of international standard hotel rooms both indoor and outdoor has fulfilled the prerequisites of ASHRAE, Thermal Environmental Conditions for Human Occupancy (Standard 55-66).Indoor air temperature of the five hotels observed was between 28.85 °C to 29.54 °C, with the air temperature approaching the comfort zone ranging from 20.5 °C to 27.1 °C. The outdoor air temperature of international standard hotel room space observed is on average range between 28.42 °C to 40.52 °C, with a standard deviation ranging from 0.01 to 0.44. The maximum value is between 28.45 °C to 41.41 °C and a minimum value is 28.40 °C to 39.87 °C. Solar radiation on international standard hotel building observed is in an average range between 32.79 watts / m2 to 769.75 watts / m2, with a standard deviation ranging from 0.95 to 285.43 watts / m2. The maximum value is between 36.37 to 918.97 watts / m2 and a minimum value is between 30.08 to 715.63 watts / m2. Solar radiation has a major influence in changing the indoor thermal comfort temperature in hotel rooms.